Maspin impairs the function of endothelial cells: an implying pathway of preeclampsia - Ying Zhang; Hao Liu; Xinwei Shi; Fuyuan Qiao; Wanjiang Zeng; Ling Feng; Dongrui Deng; Haiyi Liu; Yuanyuan Wu (BMC, 2017)
Abstract Backgroud Widespread endothelial injury contributes to the occurrence of preeclampsia. Maspin, first identified as a tumor suppressor, plays a critical role in cell invasion and angiogenesis. Our previous studies found that the expression of maspin was increased in preeclampsic placenta. In this research, we studied the function of human umbilical vein endothelial cells (HUVECs) to explore the role and possible mechanism of maspin gene in the pathogenesis of preeclampsia. Methods HUVECs were treated with different concentration of recombinant human maspin protein (r-maspin) during normoxia and hypoxia, we detected the proliferation, apoptosis, migration and tube formation of HUVECs. We also assessed nitride oxide (NO) synthesis and the expression of matrix metalloproteinase 2 (MMP2) to further explore the underlying molecular mechanism. Results There was only slight maspin expression at mRNA level in HUVECs. Treated HUVECs with r-maspin, the proliferation of HUVECs was significantly promoted both under normoxia and hypoxia. The tubes formed by HUVECs were significantly inhibited and NO synthesis was significantly reduced by r-maspin. Meantime, r-maspin also inhibited MMP2 expression and activity in HUVECs. However, there was no significant change in the migration and apoptosis of HUVECs. Conclusions Maspin may be an important participant for mediating endothelial function and ultimately leads to the occurence of preeclamsia.